Management of Patients with Cancer Conditions from a Multidisciplinary Approach - Ana Lourdes Vasallo Díaz; Dayana Calzada Urquiola; Alejandro Díaz González (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
The First Virtual Oncology Conference was held at the Dr. Gustavo Aldereguía Lima University General Hospital in the Cienfuegos province last June 2021. This activity took place during the commemoration of the 42nd founding anniversary of this important health institution. The Seminar discussed the research results related to patients with cancer diseases and their management from a multidisciplinary perspective, in addition to analyzing those cases of interest to health professionals from this specialty. The aim of this scientific event is to provide the most advanced knowledge to the specialists who are in charge of the diagnosis, treatment and monitoring of patients suffering from oncological diseases.